The influence of individual, environmental and organizational factors on the work stress among Indonesian nurses in Kuwait - Eko Priyanto; Tatan Sukwika; Bernard Hasibuan (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: The condition of Indonesian nurses in the Sabah Hospital Kuwait shows symptoms of nurse work stress, while the quality of service for health care facilities needs to be maintained and improved by strengthening individual, environmental and organizational factors towards optimizing the positive response of performing nurses.Purpose: To determine individual, environmental, organizational and work stress factors as well as to determine the influence of individual, environmental and organizational factors on the work stress of Indonesian nurses in Kuwait.Method: A descriptive cross-sectional observational design with multiple linear regression analysis and using a sampling technique with a total sampling of 65 nurses who work at Al Sabah Hospital in Kuwait.Results: This shows that individual factors are in the Moderate category and have an effect of 9.6% on nurses' work stress. Environmental factors are in the Moderate category and have an effect of 23.3% on the work stress of nurses. Organizational factors are in the Moderate category and have an effect of 12.7% on the work stress of nurses. The work stress of Indonesian nurses is in the Moderate category at 75.38%, high at 1.54%, and in the low category at 23.08%.Conclusion: There is a significant influence of 45.6% between individual, environmental and organizational factors on the work stress of Indonesian nurses in Sabah Hospital Kuwait while the rest is influenced by other factors.Suggestion: Hospitals need to design workshops or training programs on individual coping mechanisms and work stress management on a regular basis, organizational strengthening and upgrading of the work environment according to changing needs of the times at least every 6 months to 1 year, reporting nurses' work stress and conducting family meetings for nursing. minimize and relieve work stress at least once every 1-2 years.